Effect of Rituximab on the cognitive impairment in patients with secondary progressive multiple sclerosis - Saeideh Salehizadeh; Roghayeh Saeidi; Mohammad Ali Sahraian; Hossein Rezaei Aliabadi; Seyedeh Nafiseh Hashemi; Sharareh Sharareh; Mohammad Reza Gheini; Shaghayegh Shahmirzaei; Mahsa Owji; Abdorreza Naser Moghadasi (Babol University of Medical Sciences, 2022)
Background: The present study aimed to address the effect of Rituximab on the cognitive impairment in patients with secondary progressive MS (SPMS). Methods: The present interventional study used a convenience sampling method to select the study participants from SPMS patients. All these patients had progressive disability over the last two years before being admitted in the study. Prior to the administration of Rituximab, the minimal assessment of cognitive function in the multiple sclerosis (MACFIMS) test was performed for each patient who was a candidate to be included in this study. This test was repeated by passing 6 and 12 months from the initial treatment with Rituximab. Since the data needed for this study were obtained at different time intervals, so a linear mixed model was used for their analysis. Analysis of variance (ANOVA) was also used to investigate whether time and sex generally affect the cognitive impairments in SPMS patients. A p-value <0.05 was considered as statistically significant in this study. Results: Of the total 35 patients, 34% and 66% were men and women with a mean age of 41.33 and 41.39 years old, respectively. Rituximab showed a significant positive effect on a number of subgroups of MACFIMS test, including Controlled Oral Word Association Test (COWAT) (P-value: 0.038) and Brief Visuospatial Memory Test (BVMT-total) (P- value: 0.019). Conclusion: The present study revealed that Rituximab has a positive effect on the cognitive impairment resulted from MS in secondary progressive patients.